Untangling Stablecoin Price Stability Under Liquidity, Behavioral Contagion, And Flash Loan Vulnerabilities - Ahmad Pramutadi; Ibnu Khajar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of Decentralized Finance (DeFi) has strengthened the role of stablecoins as monetary anchors that connect volatile crypto assets with fiat-denominated value. Although conventional financial theory generally associates price stability with the adequacy of collateral and market liquidity, recent episodes of depegging demonstrate that stablecoin resilience is also shaped by behavioral contagion and technology-based vulnerabilities. This study develops an integrative empirical framework to examine the simultaneous effects of physical liquidity and market sentiment on stablecoin price stability while incorporating Flash Loan Attacks as a structural moderating mechanism. A quantitative explanatory design is employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and 1,095 daily observations covering the 2021-2023 period. The model evaluates direct relationships and interaction effects through Moderated Regression Analysis. The results indicate that both physical liquidity and market sentiment significantly support price stability, with market sentiment showing the stronger direct effect. However, the occurrence of Flash Loan Attacks weakens both relationships, demonstrating that cyber-financial exploitation can reduce the protective function of liquidity and intensify behavioral fragility. The model explains 68.6% of the variance in stablecoin price stability, highlighting the joint importance of market structure, investor psychology, and smart-contract security. These findings imply that stablecoin governance should combine adequate liquidity buffers, continuous sentiment monitoring, resilient oracle design, and real-time on-chain risk surveillance rather than relying solely on static collateral ratios.